Interventions d’André Markowicz et de Margaret Jones-Davies à propos de leur édition de Mesure pour Mesure - André Markowicz; Margaret Jones-Davies (Sillages Critiques)
This interpretation of « the duke of dark corners » stems from a study of the age-long battle between Philosophy and Eloquence which had taken a new turn in the context of the Wars of Religion. It leads to a new reading of the marriage between the Duke and Isabella. André Markowicz’s theory of translation stems from his experience as a translator of Russian literature. This explains his choice of the decasyllable in his translations of Shakespearean pentameters.